(untitled) (Research, Society and Development, 2022)
Objective: to describe the rate of falls and the degree of complexity of patient care in inpatient units and to identify the profile of the units in which the highest number of falls occurred. Methodology: cross-sectional, exploratory, documentary and descriptive study carried out in 12 units of a public hospital in Southern Brazil. Data were collected in institutional databases and analysis of medical records, being analyzed using descriptive statistics. The complexity of care was evidenced in the fall notifications and in the dependency classification. Results: falls occurred predominantly during the night shift, with elderly patients, unaccompanied, with a slight prevalence among men. In 70% there was no injury and the majority occurred in clinical units with a predominance of semi-intensive care. The study followed the guidelines of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE). Conclusion: the classification of the degree of dependence of the patients provides the management of the work of Nursing and the identification of opportunities for improvement.